Supramolecular adhesive materials from small‐molecule self‐assembly. (25th November 2020) - Shi, Chen‐Yu; Zhang, Qi; Tian, He; Qu, Da‐Hui
Abstract: Developing high‐performance adhesive materials not only aims at industrial and social requirements but also bears the fundamental importance of understanding the chemical factors of biological adhesion to develop biomimetic adhesive materials. Owing to the wide development of supramolecular chemistry, numerous supramolecular tools are exploited and proved to be reliable in the replacement of traditional covalent materials by reversible noncovalent or dynamic covalent materials. Taking advantage of these ready‐to‐use supramolecular toolboxes, supramolecular adhesive materials are rising and promising toward "smart" adhesives, that is, enabling responsiveness, reversibility, and recyclability. Compared with polymeric adhesive materials, low‐molecular‐weight adhesives feature chemically precise structure, easier engineering by molecular design, and hence higher reproducibility. However, it remains highly challenging to make high‐performance adhesive materials by low‐molecular‐weight feedstocks. This review will focus on the recent advancement in the construction of supramolecular adhesive materials by small‐molecule self‐assembly. The design guidelines and consideration on the molecular scale will be discussed and summarized on how to enhance the strength of adhesives. Meanwhile, owing to the dynamic nature of supramolecular self‐assembly, several "smart" functions of such materials will be presented, such as stimuli–responsiveness and adaptiveness. Finally, current challenges and future perspectives of this emerging field will be proposed. Abstract : Supramolecular adhesive materials are rising and promising toward "smart" adhesives, that is, enabling responsiveness, reversibility, and recyclability. Compared with polymeric adhesive materials, low molecular weight adhesives feature chemically precise structure, easier engineering by molecular design, and hence, higher reproducibility. The design guidelines and considerations on the molecular scale are discussed and summarized on how to enhance the strength of adhesives. Meanwhile, owing to the dynamic nature of supramolecular self‐assembly, several "smart" functions of such materials are presented, such as stimuli‐responsiveness and adaptiveness. Finally, current challenges and future perspectives of this emerging field are proposed.